Can the positive and negative syndrome scale (PANSS) differentiate treatment-resistant from non-treatment-resistant schizophrenia?: a factor analytic investigation based on data from the Pattern cohort study - Ramos, Rosana; Dos Santos, Bernardo; Altamura, Carlo; Bernasconi, Corrado; Corral, Ricardo; Evans, Jonathan; Malla, Ashok; Krebs, Marie-Odile; Nordstroem, Anna-Lena; Zink, Mathias; Haro, Josep Maria; Elkis, Helio (Psychiatry research, 2019)
Treatment-Resistant Schizophrenia (TRS) and Non-Treatment-Resistant Schizophrenia (NTRS) may represent different subtypes of schizophrenia. However, few studies have investigated their PANSS symptom dimensions by Exploratory (EFA) or Confirmatory (CFA). Data from the present study are derived from 1429 patients of the Pattern study. TRS was defined by the use of clozapine in the previous year whereas NTRS by the use of non-clozapine antipsychotics ("by proxy"). Factors were chosen based on the Kaiser criterion and considered valid when loadings were greater than or equal to 0.5. The fit to the data was evaluated by CFA in comparison with well-established PANSS models, using fit indexes. The EFA yielded similar five-factor model in both groups: Negative, Positive, Anxiety/Depression, Cognitive and Excited. CFA showed a satisfactory, but not perfect, fit to the data, as compared with the previous PANSS factor analytic models. Despite the limitations regarding the ‘by proxy’ definition of TRS, the results of the present study show that there are no differences in the factorial structure of PANSS in patients with TRS and NTRS.
Available online 08 May 2019
Gesehen am 19.02.2020